Razmislek in sodna praksa Vrhovnega sodišča o nekaterih aktualnih vprašanjih odškodninskega prava v zvezi z nepremoženjsko škodo - Božič-Penko, Ana (Pravni letopis, 2016)
Law of obligations is a live law. This is particularly true for tort law. It protects pecuniary and non-pecuniary values. Non-pecuniary values and the ways of breaching them are changing over time and due to social circumstances. Legal protection should track these changes and adapt to them. This is possible to a large extent without changing the obligation regulations but merely by using the right interpretation. Judicial practice plays an important role in it. Thanks to judicial practice, the term non-pecuniary damage has recently been introduced. The article deals with current issues of non-pecuniary damage in the recent practice of the Supreme Court and particularly with the question whether the Code of Obligations conceives legally recognized forms of non-pecuniary damage and the beneficiaries of compensation taxatively or personally, and with the question whether the victim is entitled to compensation for non-pecuniary damage due to the breach of contract. On the issue of heritability of compensation for non-pecuniary damage, it underlines the decision of the Constitutional Court UI-88 / 15-9, Up-684 / 12-32 dated 15. 10. 2015, which proved that provision of Article 201 of the formerly valid Law of Obligations was unconstitutional because it conditioned the heritability of compensation with the finality of judgement.
Keywords: kršenje; nepremoženjska škoda; odškodnina; odškodninsko pravo; pogodbe; sodna praksa